Utilization of Plants as Traditional Food by The Dayak Iban Community of Mensiau Village, Batang Lupar District, Kapuas Hulu Regency - Wulandari, Reine Suci; Muflihati, Muflihati; Libertus Luben Aden; Wahdina, Wahdina (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
The Iban Dayak people use forest plants from non-timber forest products (NTFPs) as traditional food. The purpose of the study was to study traditional foods and to record the types of forest plants used, processing methods, and efforts to maintain their sustainability by the Dayak Iban community in Mensiau Village, Batang Lupar District, Kapuas Hulu Regency. Interviews with the determination of respondents by purposive sampling. The Iban Dayak tribe has 14 types of traditional foods that are used for daily needs, certain holidays, and traditional ceremonies using 56 types of forest plants (33 families). The families with the most species were 8 species of Arecaceae, 6 species of Zingiberaceae, and 5 species of Poaceae. A total of 37 species have the greatest usefulness value (UV) (1). The most widely used habitus were herbs (26,78%) The most widely used plant parts were leaves (49,25%). How to process it by cooking boiled, sauteed, and eaten directly (lalap). Conservation efforts are carried out based on the local wisdom of the Iban Dayak community with certain rules and carry out plant cultivation in forests, fields, gardens, and house yards.